Career Information System of Iowa Activity Report for FY 1975 - Ericksen, Erik.; Iowa State Dept. of Public Instruction, Des Moines. Guidance Services Section ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
In order for youth to make realistic and informed career choices, they need ready access to relevant, up-to-date occupational information. These documents outline and describe the development of such a career information system in Iowa, created through the state board of public instruction. The career information system is three basic services: A needle-sort (manual) delivery of occupational information; a computerized delivery of this information; and career education inservice activities for school districts. Each of the 252 job briefs specifies qualifications, work descriptions, earnings and benefits, advantages and disadvantages, employment and advancement opportunities, preparation required and training available, and additional sources of information. Notice of training opportunities in Iowa for the various occupations is also readily accessible. The report describes activities in the area of evaluation of the system to date. The report has a number of appendices, including lists of subscribers to the system and a statistical summary of user activity. (NG)
ERIC Note: Because of reproduction problems, Appendix E, 'CISI Information Packet,' has been removed from this document.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Choice; Career Counseling; Career Education; Career Planning; Careers; Employment Opportunities; Evaluation; Information Systems; Occupational Information; Secondary Education; State Programs; Reports, Descriptive